Opportunities for improving patient experiences among medical travellers from Canada's far north: a mixed-methods study. Issue 12 (4th December 2019) - Kerber, Kate; Kolahdooz, Fariba; Otway, Meeka; Laboucan, Melinda; Jang, Se Lim; Lawrence, Sue; Aronyk, Suzanne; Quinn, Matthew; Irlbacher-Fox, Stephanie; Milligan, Crystal; Broadhead, Sabrina; DeLancey, Debbie; et al.
Abstract : Objectives: This paper explores patient experiences and identifies barriers and opportunities for improving access to healthcare for patients from the Canadian north who travel to receive medical care in a Southern province. Design: A mixed-methods, cross-sectional study involved one-on-one interviews, focus group discussions and key informant interviews. Participants: 52 one-on-one interviews with Northwest Territories (NWT) patients and patient escorts and two focus group discussions (n=10). Fourteen key informant interviews were conducted with health workers, programme managers and staff of community organisations providing services for out-of-province patients. A Community Advisory Board guided the development of the questionnaires and interpretation of results. Results: Respondents were satisfied with the care received overall, but described unnecessary burdens and bureaucratic challenges throughout the travel process. Themes relating to access to healthcare included: plans and logistics for travel; level of communication between services; clarity around jurisdiction and responsibility for care; indirect costs of travel and direct costs of uninsured services; and having a patient escort or advocate available to assist with appointments and navigate the system. Three themes related to healthcare experiences included: cultural awareness, respect and caring, and medical translation. Respondents provided suggestions to improve access to care. Conclusions: Patients from NWT need more information and support before and during travel. Ensuring that medical travellers and escorts are prepared before departing, that healthcare providers engage in culturally appropriate communication and connecting travellers to support services on arrival have the potential to improve medical travel experiences.